3, 6‐Anhydro‐l‐galactonate cycloisomerase from Vibrio sp. strain EJY3: crystallization and X‐ray crystallographic analysis. Issue 9 (6th September 2017) - Lee, Saeyoung; Yun, Eun Ju; Kim, Kyoung Heon; Kim, Hye-Yeon; Choi, In-Geol
Abstract : 3, 6‐Anhydro‐l ‐galactonate cycloisomerase (ACI) is a second‐step enzyme in the metabolic pathway of 3, 6‐anhydro‐l ‐galactose. Structural analysis of ACI is crucial in order to elucidate its function, substrate specificity and reaction mechanism at the molecular level. Abstract : 3, 6‐Anhydro‐l ‐galactonate cycloisomerase (ACI), which is found in the marine bacterium Vibrio sp. strain EJY3, converts 3, 6‐anhydro‐l ‐galactonate into 2‐keto‐3‐deoxygalactonate. ACI is a key enzyme in the metabolic pathway of 3, 6‐anhydro‐l ‐galactose (AHG). Study of AHG metabolism is important for the efficient fermentation of agar and biofuel production, because AHG is a sugar that is non‐fermentable by commercial microorganisms. The aci gene from Vibrio sp. strain EJY3 was cloned, and the recombinant protein was overexpressed and crystallized in order to determine the structure and understand the function of the protein. The crystals diffracted to 2.2 Å resolution and belonged to space group P 41 21 2 or P 43 21 2, with unit‐cell parameters a = b = 87.9, c = 143.5 Å. The Matthews coefficient was 2.3 Å 3  Da −1, with a solvent content of 47%.